Evaluating the Dietary and Nutritional Apps in the Google Play Store - Schumer, Harleigh (Healthc Inform Res, 2018)
OBJECTIVES: The objective of this study was to evaluate the features of diet and nutrition apps available in the Google Play Store. METHODS: A search was conducted in August 2017 using the Google Play Store database to identify apps related to diet and nutrition. Terms entered into the app search engine included ‘diet apps’ and ‘nutrition apps’. The first 50 apps resulting from each search term was assessed. Duplicates were removed, and a comparative analysis was performed on the remaining diet and nutrition apps. RESULTS: A total of 86 diet and nutrition apps were identified. One hundred percent (n = 86) of the apps retrieved were freely available. More than half of the apps were applicable to a target user group of all ages (94%, n = 81). Stratified analysis across unique diet and nutrition apps (total, n = 72) showed a higher average rating for the diet apps (4.4) in comparison to that for the nutrition apps (4.3). Diet apps were more likely to be recently updated than the nutrition apps (72% vs. 66%), and diet apps were more likely to feature app purchase than nutrition apps (36% vs. 19%). The average rating was slightly higher for diet apps not featuring in-app purchases, but ratings were similar for the nutrition apps. CONCLUSIONS: A centralized resource is needed that can provide information on health-related apps to allow for systematic evaluation of their effectiveness. Further research needs to examine improved methods of designing app-store platforms and presenting the available apps to properly guide users in app selection.